2019
DOI: 10.1186/s12913-019-4677-x
|View full text |Cite
|
Sign up to set email alerts
|

A guideline for the prevention and management of Fetal Alcohol Spectrum Disorder in South Africa

Abstract: BackgroundFetal Alcohol Spectrum Disorder (FASD) is a public health problem globally, with South Africa having the highest recorded prevalence of all countries. Government programmes to prevent and manage FASD remain limited because of the lack of a specific policy. Herein, we developed a guideline to inform policy on the prevention and management of FASD in South Africa.MethodsWe applied a modified version of the World Health Organization’s approach to guideline development in three phases. In the first phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…In the Delphi study (20), the experts identified measures that could be included for the prevention and management of FASD in South Africa based on the refined prototype. Some of the guiding principles and approaches include collaboration, consider the family as a unit, human right-based, holistic, evidence-based, culturally diverse and sensitive, considering input from individuals with FASD and their families and addressed social determinant of health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Delphi study (20), the experts identified measures that could be included for the prevention and management of FASD in South Africa based on the refined prototype. Some of the guiding principles and approaches include collaboration, consider the family as a unit, human right-based, holistic, evidence-based, culturally diverse and sensitive, considering input from individuals with FASD and their families and addressed social determinant of health.…”
Section: Resultsmentioning
confidence: 99%
“…We adapted the WHO's approach to guideline development (18,19). The study was conducted in three phases (Figure 1) (20). In the first phase, two qualitative studies were conducted (indepth interviews with policymakers and focus group discussions with service providers).…”
Section: Policy Options and Implications Methodsmentioning
confidence: 99%
“…Alcohol and tobacco are well-known teratogens and can cause an array of poor health outcomes. South Africa has the highest rate of foetal alcohol spectrum disorder (FASD) in the world [ 23 ], and almost one in ten participants (9.0%) in the current study consumed alcohol during the current pregnancy. Ideally, pregnant women who consume alcohol should consume higher amounts of choline, because it has been shown that higher choline intake may protect against some of the adverse consequences of FASD [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because these clauses are generic and poorly implemented or translated into effective programs and interventions. Some policymakers associate the development of a separate policy to increase commitment to addressing the incessant rise in FASD prevalence (Adebiyi et al, 2021;Adebiyi et al, 2019d;.…”
Section: Discussionmentioning
confidence: 99%